Edukasi Literasi Digital Untuk Peningkatan Kualitas Siswa Dalam Memahami Internet of Things (IoT) dan Profesi dalam Bidang IT - Mandela, Nelson; Pradana, Awang; Junior, Saputra; Gresia, Celsia; Rizky, Muhammad; Rahmat, Rizal; Deswita, Felisia (Jurnal Pengabdian Masyarakat - PIMAS, 2024)
This community service is carried out at SMPN 14 Tarakan. This service activity aims to increase the digital literacy of junior high school students by using ICT-based learning media. This service activity has the aim of realizing that students at SMPN 14 Tarakan have basic knowledge in the field of technology, especially in the IT field. This activity is carried out in the form of socialization regarding technological advances in the current digital era which makes everyone have to adapt to these technological developments and the impact of these developments. this technology in the world of education as well as an introduction to internet of things technology, how the internet works and smart ways to use the internet, as well as an introduction to professions in the IT world. The final outcome that will be achieved from this service activity is increasing students' abilities in using computers as a tool for developing students' creativity in the world of education, apart from that, students also have literacy in the world of technology. The final outcome of this service activity is the publication of the results of this service in a service journal. This service activity is carried out in two stages, namely: The first stage is the planning and preparation stage. At this stage, an analysis of student needs is carried out as well as preparation of learning materials and methods. The second stage is the implementation stage. At this stage, students are socialized about digital literacy. This training uses ICT-based learning media, such as videos, animations and simulations.The results of this service show that the digital literacy of students at SMPN 14 Tarakan increased after attending the training. Increasing student digital literacy can be seen from Students' ability to understand the concepts and how technology works ,Students' ability to access information and resources effectively,Students' ability to analyze and evaluate information